Paclitaxel-induced arterial wall toxicity and inflammation: tissue uptake in various dose densities in a minipig model - Radeleff, Boris; Lopez-Benitez, Ruben; Stampfl, Ulrike; Stampfl, Sibylle; Sommer, Christof-Matthias; Thierjung, Heidi; Berger, Irina; Kauffmann, Günter W.; Richter, Götz Martin (Journal of vascular and interventional radiology, 2010)
Purpose - Paclitaxel is an antiproliferative agent in drug-eluting stents with largely unknown tissue interaction. Toxicity might result from overdosage and/or accumulation. Part 1 of this two-step study investigated how paclitaxel uptake depends on dose density, coronary drug transfer kinetics, and elution efficacy. - Materials and Methods - With cobalt chromium stents and Polyzene-F nanoscale coating, low, intermediate, and high paclitaxel dose densities (25 μg, 50 μg, and 150 μg per stent) were investigated in porcine right coronary arteries (RCAs). Coronary and myocardial tissue concentration measurements and determination of on-stent paclitaxel and plasma concentrations were performed at 2, 8, 24, and 72 hours. - Results - For all stents, uptake was similar at all time intervals (paclitaxel RCA concentration range, 1,610-33,300 ng). Low- and intermediate-dose stents showed similar RCA concentrations, but those for high-dose stents were three times greater. Residual on-stent paclitaxel concentration was not time-dependent, at 33.3% on low-, 30.6% on intermediate-, and 17.4% on high-dose stents. Paclitaxel was measurable in only the plasma immediately after stent placement, with a linear dose relationship and a timely regression: measurements in high-dose stents were 0.0454-0.656 ng/mL at 1 minute and 0.0329-0.0879 ng/mL at 5 minutes. Untreated control samples of the left coronary artery showed a linear dose-dependent concentration (12.6 ng/g, 21.2 ng/g, and 85.2 ng/g). - Conclusions - Overall coronary paclitaxel uptake is fairly independent from the baseline overall dose density and, hence, depends on immediate binding mechanisms of the arterial wall. This is supported by the fact that, regardless of the applied dose density, the kinetics of paclitaxel uptake did not follow an exposure time pattern.